Design and analysis of piping system for an open channel flume’s flow - Hamdi Abdullah, Mohammed Mudhsh (2013)
The increase on the usage of non-renewable energy has caused high demanding on energy supplies. This demand is highly needed for the industrial, transportation, domestic usage and etc. Shortage in the non-renewable energy had caused human to find other alternatives to generate energy. Hence, this research is aim to develop a flume, that later use to generate electricity. However, researcher only focuses on the design and analysis of the piping system of the flume. The objectives of this research is to design piping system of an open channel with less head losses and simulate it using CFD for only single phase perform (not free service), to evaluate the pressure drop in the pipes and to analyses and determine the head losses in the pipe. The instrument used is Solid Work 2012 for technical drawing of the piping system and Computational Fluid Dynamics (CFD) for simulation of the design and analysis. There are four designs of piping system that had been produce which is Design A, Design B, Design C and Design D, the properties measured for all four designs are pressure drop, percentage pressure drop, head loss and velocity. Design A; average percentage of pressure drop is 40.2%, average head loss which is 2.7 m, velocity; inlet velocity is 8.84 m/s and average outlet velocity is 8.75 m/s. Design B; average percentage of pressure drop is 53.6 %, average head loss which is 5.8 m, velocity; inlet velocity is 8.84 m/s and average outlet velocity is 14.31 m/s. Design C; percentage of pressure drop is 38.4 % ,head loss which is 4.4 m, velocity; inlet velocity is 8.84 m/s and outlet velocity is 11.76 m/s. Designs D; percentage of pressure drop is 30.7%, head loss which is 3.1 m, velocity; inlet velocity is 8.84 m/s and outlet velocity is 12.03 m/s. The best design is determined by less percentage of pressure drops, hence from the research findings Design D is the best design since it has the less percentage of pressure drop.